Biotribocorrosion performance of titanium alloy Ti-6A1-4V and stainless steel 316L under simulated body environment [electronic resource] - 367063 Juliawati Alias; Fakulti Kejuruteraan Mekanikal (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana (Kejuruteraan Bahan)) - Universiti Teknologi Malaysia, 2008